Efeitos de extrato e composto ativo da Centella asiatica em comportamento tipo depressivo, estresse oxidativo e inflamação em ratos submetidos a privação maternal - Oliveira, Tácio de (2022)
The medicinal species Centella asiatica and its isolated active principles (madecassic acid, madecasoid, madecassoside) have been studied in the major depressive disorder (MDD) context, being related to antidepressant and neuroprotective effects. Several studies have reported anti-inflammatory, antioxidant, and nootropic effects. MDD is related to increased inflammatory cytokines and oxidative stress in the central nervous system (CNS) and periphery. Maternal deprivation (PM) in baby rats is an animal model of the reproduction of behaviors and biological mechanisms related to MDD in humans. Therefore, this work used rats submitted to PM in the first days of life and treated in adulthood with Centella asiatica extract, or madecassic acid (AM), or escitalopram (ESC), as described below: 5 groups with 10 rats each, being group 1 the stress-free control + vehicle (control), group 2 PM + vehicle (negative control), group 3 PM + ESC (positive control), group 4 PM + Centella asiatica extract, group 5 PM + AM. The animals were submitted to the PM for 10 days from the second day of birth. At 60 days of age, they were treated for 14 days. At the end of the period, behavioral tests, and euthanasia were performed to measure the following parameters: myeloperoxidase (MPO) in blood serum and hippocampus, thiobarbituric acid reactive substances (TBARS) (serum and hippocampus), interleukin-1β (IL-1β), interleukin-6 (IL-6) (hippocampus). The PM induced depressive-like behaviors in adulthood and increased inflammation and oxidative stress. Intervention with extracts of ESC, AM, and Centella asiatica yielded the reversal of depressive-like behaviors and significantly reduced serum MPO levels. Treatment with AM and ESC managed to maintain serum and hippocampal TBARS levels equal to the control group without PM. Treatment with Centella asiatica extract did not significantly reduce TBARS levels in serum and hippocampus. Regarding IL1β, ESC and AM reversed levels in the hippocampus. Centella asiatica extract did not decrease substantially. All treatments reversed the increase in IL-6 in the hippocampus. These results corroborate studies with other protocols, suggesting a potential antidepressant effect, possibly involving a reduction in oxidative stress and inflammation.